Further Standardization in the Aneurysm Clip: The Effects of Occlusal Depth on the Outcome of Spinal Cord Injury in Rats. Issue 3 (1st February 2018) - Rong, Hui; Liu, Yue; Zhao, Zhibin; Feng, Jiying; Sun, Rao; Ma, Zhengliang; Gu, Xiaoping
Abstract : Study Design: Experimental study. Objective: To evaluate the relationship between clip occlusal depth and functional and histological outcome measures in a rat model of thoracic spinal cord injury (SCI). Summary of Background Data: Aneurysm clip compression is a proven model of contusion-compression SCI, but the relationship between clip depth and outcomes in thoracic SCI is unknown. Methods: A single aneurysm clip was applied to the spinal cord at thoracic vertebra 10 for 1 minute with an occlusal depth of 2, 6, or 10 mm. The actual compression force was measured using a self-made pulling method. Locomotor function was assessed for 28 days using Basso, Beattie, and Bresnahan (BBB) and inclined plane test (IPT) scores. We then used hematoxylin-eosin and Luxol fast blue staining to histologically quantify cavitation formation, preserved white matter, and preserved grey matter. Results: Greater occlusal compression depths caused greater actual compression forces and worsened functional and histological recovery. The 2- and 10-mm clip injury groups had significantly different BBB and ITP scores; cavitation, preserved white matter, and preserved grey matter volumes; and actual force measures ( P < 0.05). Conclusion: Our findings show that the occlusal depth of clip compression correlates with actual compression force and recovery impairment. Level of Evidence: 1